The volatile fraction of the German chamomile (Matricária recutita L.) - Teixeira, Iara Elizabeth Abi-Zaid (2020)
The German chamomile (Matricaria recutita L.) is a plant of the Asteraceae family that is widely used by the world population due to its characteristic flavor and aroma and striking medicinal properties like its calming, sedative, anti-inflammatory, antimicrobial and carminative actions. The flavor, aroma and part of the medicinal properties of this herb can be associated with the composition of its volatile fraction. Thus, this bibliographic review sought to establish the characteristics of the volatile fraction of German chamomile, indicating the levels, sensory and pharmacological properties of its main constituents. This information was obtained from different databases available online, with the selection of forty-three scientific articles (last three decades) that specifically dealt with the volatile compounds of this herb.